Ethiopian Digital AgroClimate Advisory Platform (EDACaP) Technical Working Document - Brief version - Ahmed, Jemal Seid; Demissie, Teferi Dejene; Tesfaye, Kindie; Tamene, Lulseged D.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
One of the main problems for Ethiopian smallholder farmers is a general lack of reliable weather and climate forecasts. The lack of climate forecasting information becomes more and more challenging for smallholder farmers as the variability in weather increases, which results in an unpredictable and highly variable agricultural yield. To address this challenge, the first phase of the platform is to generate and provide relatively better-quality local weather forecasts. To achieve this, we are working closely together with the Ethiopian National Meteorology Agency (NMA) and the International Research Institute for Climate and Society (IRI) to improve seasonal and sub-seasonal climate prediction in Ethiopia.